1996
DOI: 10.1039/cc9960000179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and surfactant properties of novel fluoroalkylated amphiphilic oligomers

Abstract: New fluoroalkylated oligomers containing morpholino groups are prepared by the reactions of fluoroalkanoyl peroxides with acryloyl morpholine; these oligomers show a good solubility in not only water but also common organic solvents, including non-polar solvents, and are applicable to non-ionic fluorinated amphiphilic oligosurfactants owing to reducing the surface tension of both water and in particular rn-xylene quite effectively .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…N ‐(1,1‐Dimethyl‐3‐oxobutyl)acrylamide (DOBAA) and N,N ‐dimethylacrylamide (DMAA) were used as received from Kyowa Hakko Kogyou Co., Ltd. (Tokyo, Japan) and Kohjin Co., Ltd. (Tokyo, Japan), respectively. Fluoroalkyl end‐capped DOBAA and DMAA oligomers were prepared by the reactions of fluoroalkanoyl peroxides with the corresponding monomers according to our previously reported method 9, 10…”
Section: Methodsmentioning
confidence: 99%
“…N ‐(1,1‐Dimethyl‐3‐oxobutyl)acrylamide (DOBAA) and N,N ‐dimethylacrylamide (DMAA) were used as received from Kyowa Hakko Kogyou Co., Ltd. (Tokyo, Japan) and Kohjin Co., Ltd. (Tokyo, Japan), respectively. Fluoroalkyl end‐capped DOBAA and DMAA oligomers were prepared by the reactions of fluoroalkanoyl peroxides with the corresponding monomers according to our previously reported method 9, 10…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the molecular weights of these oligomers measured by GPC were found to decrease with increasing concentration of the eluents. Considering the fact that water-soluble fluoroalkyl end-capped oligomers such as fluoroalkyl end-capped acrylic acid (ACA) oligomers and ACMO oligomers can easily form molecular aggregates owing to the strong aggregations of end-capped fluoroalkyl segments in aqueous solutions, 11 it is suggested that the obtained values by GPC indicate the apparent molecular weights. In fact, we could measure the molecular weights of some oligomers in Table I by using a 50 mM H 2 NC(CH 2 OH) 3 and 1M NaCl solution as the eluent.…”
Section: Synthesis Of Fluoroalkyl End-capped Oligomers Containing Pemmentioning
confidence: 99%
“…Indeed, these PFOA or PFOS have been synthesized from tetrafluoroethylene (TFE) telomers. 1,8 Although short perfluorinated chains (C4) 25 or oligo(hexafluoropropylene oxide) [26][27][28][29] -based surfactants have already led to original nonbioaccumulable alternatives to PFOA, it was of interest to find new derivatives.…”
Section: Introductionmentioning
confidence: 99%